Cross-modal cueing effects of visuospatial attention on conscious somatosensory perception - Deniz Doruk; Lorena Chanes; Alejandra Malavera; Lotfi B. Merabet; Antoni Valero-Cabré; Felipe Fregni (Heliyon, 2018)
Objective: The impact of visuospatial attention on perception with supraliminal stimuli and stimuli at the threshold of conscious perception has been previously investigated. In this study, we assess the cross-modal effects of visuospatial attention on conscious perception for near-threshold somatosensory stimuli applied to the face. Methods: Fifteen healthy participants completed two sessions of a near-threshold cross-modality cue-target discrimination/conscious detection paradigm. Each trial began with an endogenous visuospatial cue that predicted the location of a weak near-threshold electrical pulse delivered to the right or left cheek with high probability (∼75%). Participants then completed two tasks: first, a forced-choice somatosensory discrimination task (felt once or twice?) and then, a somatosensory conscious detection task (did you feel the stimulus and, if yes, where (left/right)?). Somatosensory discrimination was evaluated with the response reaction times of correctly detected targets, whereas the somatosensory conscious detection was quantified using perceptual sensitivity (d′) and response bias (beta). A 2 × 2 repeated measures ANOVA was used for statistical analysis. Results: In the somatosensory discrimination task (1st task), participants were significantly faster in responding to correctly detected targets (p < 0.001). In the somatosensory conscious detection task (2nd task), a significant effect of visuospatial attention on response bias (p = 0.008) was observed, suggesting that participants had a less strict criterion for stimuli preceded by spatially valid than invalid visuospatial cues. Conclusions: We showed that spatial attention has the potential to modulate the discrimination and the conscious detection of near-threshold somatosensory stimuli as measured, respectively, by a reduction of reaction times and a shift in response bias toward less conservative responses when the cue predicted stimulus location. A shift in response bias indicates possible effects of spatial attention on internal decision processes. The lack of significant results in perceptual sensitivity (d′) could be due to weaker effects of endogenous attention on perception.